(untitled) (Journal of the College of Basic Education, 2022)
The subject of philosophy and psychology in secondary schools is a new course introduced starting from the academic year 2009-2010 and the teachers who teach this subject are not experienced and specialized, but the majority are among the teachers whose full teaching quota has not been covered in their specialization minute, which makes the administration embarrassed by their matter, which prompts them to complete their quorum in part of the classes of this subject, noting that it is one of the most important courses that were introduced in the aforementioned academic year, because students in educational institutes and colleges were suddenly surprised by a subject New to their mental structures, called the principles of psychology, or general psychology, or educational psychology due to their lack of background in the previous curricula decisions for such an important subject, and in order to prepare and scientifically and psychologically qualify them to accept the subject of psychology and to accelerate the process of professional adaptation and appropriate social acceptance